The victory of Ayacucho marks the assumption of the republican ideology in Peru. Interview with Víctor Peralta Ruiz - Pérez Garay, Carlos Alberto (2024)
This interview was carried out on Wednesday, March 13, in the office of the aforementioned researcher, at the Center for Human and Social Sciences, located at Albasanz Street, 26, San Blas, Canillejas, Madrid. The interview focused on the process of Peru’s independence between 1821 and 1824, the prominence of the liberators, San Martín, Bolívar, the sources consulted in their research on emancipation and the commemoration of the Bicentennial of the Battle of Ayacucho, the December 9, 2024.